The philosophical foundation of ideal-type bureaucracy - Santhitiwanich, Arunee (Kasetsart Journal of Social Sciences, 2017)
Scholars believe that Max Weber’s ideal-type bureaucracy is based on a realist idea, which assumes that such a bureaucratic system exists. I, however, argue that the notion of ideal-type bureaucracy is actually based on constructivism. The ideal-type bureaucracy was invented to understand administrative work in the early 20th century, which was built on the idea of maximizing rationality. To make this work, Weber deliberately excludes some uncontrollable factors from his model, notably human aspects. This exclusion, in turn, causes problems when the model is used. In this article, I utilize a structure-agency framework to demonstrate the weaknesses in Weber’s ideal-type bureaucracy, which are caused by not taking human factors into consideration. By using such a framework, the article reveals that a human’s limitations to conform to the designed structure make Weber’s ideal-type bureaucracy simply an unrealistic ideal.